Autoantibody Response Toward Chromatin in Patients With Juvenile Idiopathic Arthritis - Pitkänen, Viola; Remes-Pakarinen, Terhi; Vähäsalo, Paula; Möttönen, Milja; Grönlund, Minna-Maija; Arvonen, Miika; Knip, Mikael; Veijola, Riitta; Toppari, Jorma; Ilonen, Jorma; Lempainen, Johanna; Schroderus, Anna-Mari; et al. (John Wiley & Sons, 2026)
Objective. Patients with juvenile idiopathic arthritis (JIA) frequently exhibit antinuclear antibodies (ANAs), but the specific antigen target recognized by them and the presence of additional autoantibody specificities in patients with JIA remains elusive.
Methods. Plasma samples from 110 untreated patients with active JIA, as well as from 14 children with unspecified arthritis and 151 age- and sex-matched healthy children, were analyzed with multiple modern clinical-grade autoantibody assays, including automated indirect immunofluorescence to screen for ANAs with HEp-2 cells, and specific immune assays to detect reactivity to individual autoantigens. In addition, a HuProt proteome microarray was used to screen for novel autoantibody targets in plasma samples from five patients with ANA-positive JIA and four ANA-negative healthy controls.
Results. Homogeneous nuclear ANA staining, indicating reactivity toward chromatin, was detected in most (61.8%) patients with JIA but rarely in healthy controls (2.6%; P < 0.0001). No antibody reactivity to specific nuclear antigens or other autoantigens associated with connective tissue diseases was detected. However, 20% of patients with JIA harbored antibodies against double-stranded DNA (dsDNA)-nucleosome complexes (compared with 2.6% of controls, P < 0.0001). Finally, the proteome microarray revealed core histone H2A variant H2AFY, part of the nucleosome, to be the most widely recognized human protein by autoantibodies of patients with JIA.
Conclusion. Autoantibody reactivity in JIA primarily targets chromatin, but the epitopes targeted are likely either posttranslationally modified or multimolecule epitopes, such as dsDNA-nucleosome complexes, rather than epitopes on individual native proteins or purified dsDNA.